The Quantitative Indices of ERCC1 Expression in Serous Ovarian Cancer Tissue and the Efficacy of First-Line Platinum-Based Chemotherapy - T. A. Bogush; M. B. Stenina; E. A. Bogush; V. T. Zarkua; S. A. Kalyuzhny; I. A. Mamichev; A. S. Tyulyandina; S. A. Tyulyandin (Антибиотики и Химиотерапия, 2020)
Platinum-based drugs are widely used in clinical practice. Their efficacy varies widely among patients, which may be due to a disruption of the expression of ERCC1 - excision repair protein. In the prospective study a strictly quantitative analysis of the ERCC1 protein expression was carried out in surgical biopsy specimens of serous ovarian cancer by flow cytometry. ERCC1 expression was revealed in 100% of cases, but the expression level of the marker (the percentage of cells expressing ERCC1) varied significantly between tumors: the minimum was 40%, the maximum - 77%, the median - 64.5%; the average - 64.3+9.0%. The analysis of the Kaplan-Mayer curves showed an inverse relationship between the expression of ERCC1 and the duration of the relapse-free period during a 40-month follow-up after the first-line platinum-taxane chemotherapy (p